Technology-Driven Resource Utilization and Integration to Enhance Firm Performance - Nasution, Muhammad Dharma Tuah Putra; Rossanty, Yossie; Harahap, Ramadhan; Tanjung, Aulia Ramadhan; Nasution, Thorique Akbar Maulana (Pandawan, 2026)
Rapid digital transformation has increased the need for firms to optimize how technological resources are utilized and integrated to enhance performance, particularly among Small and Medium-sized Enterprises (SMEs) facing resource constraints. Although prior research highlights the value of digital adoption, less is known about how resource integration mechanisms convert technology-driven utilization into sustainable performance outcomes. This study aims to examine the effect of technology-driven resource utilization on firm performance and to test the mediating role of resource integration within the Resource-Based View (RBV) framework. A quantitative research design was applied using survey data collected from 233 firms undergoing digital transformation across various industries. The hypothesized relationships were analyzed using Structural Equation Modeling (SEM) with SmartPLS. The analysis followed standard PLS-SEM procedures, including measurement model assessment for reliability and convergent validity, and structural model evaluation to test path significance and mediation effects. The results show that technology-driven resource utilization has a significant positive effect on firm performance. Resource integration also significantly improves firm performance and partially mediates the relationship between resource utilization and performance, indicating that digital resources contribute more effectively when embedded into coordination routines, aligned workflows, and knowledge-sharing mechanisms. This study concludes that dynamic resource integration is a critical capability for translating technology-driven resource utilization into sustainable firm performance, extending RBV by emphasizing integration capability as a strategic asset. Limitations include the cross-sectional design and SME-focused sample; future studies should employ longitudinal designs and broader industry contexts.